HUBUNGAN KELINCAHAN DENGAN HASIL FOOTWORK PADA ATLET PUTRA BULUTANGKIS RIAU ANDALAN PULP AND PAPER PANGKALAN KERINCI - Rahmi Shintya Salmiati; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem of this research is when playing game material (sparing), it is often seen that players miss the ball because they are slow to turn their bodies to receive the next ball effect to the agility of players who are not good. The purpose is to find out how much the corelation of agility with the results of footwork in the athletes male of Badminton Riau Andalan Pulp And Paper Pangkalan Kerinci, amounting to 5 people. This research technique uses total sampling, where the total population is sampled. This research uses correlation techniques. Then, the test data used the normality test, the correlation product moment test, a significant test α = 0.05. Normality test variable X, L0max (0.1446) <Ltabel (0.337), and variable normality test Y, L0max (0.2186) <Ltabel (0.337) in other words the level of trust 95% of normal data and research conclusions show: where there is a relationship a significant relationship between agility and footwork results, with a correlation r = 0.953 where rhitung> rtabel 0.953> 0.950. Where the magnitude of the correlation coefficient when viewed from the level of relationship (interpretation) the value of r is having a very strong level of relationship with the interpretation of the r value of 0.80 - 1,000.Key Words: Correlation, Agility, Footwork Results.